2014
DOI: 10.1080/02626667.2014.887203
|View full text |Cite
|
Sign up to set email alerts
|

A watershed-scale study of climate change impacts on groundwater recharge (Annapolis Valley, Nova Scotia, Canada)

Abstract: The potential impacts of future climate change on the evolution of groundwater recharge are examined at a local scale for a 546-km 2 watershed in eastern Canada. Recharge is estimated using the infiltration model Hydrologic Evaluation of Landfill Performance (HELP), with inputs derived from five climate runs generated by a regional climate model in combination with the A2 greenhouse gas emissions scenario. The model runs project an increase in annual recharge over the 2041-2070 period. On a seasonal basis, how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
17
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 30 publications
2
17
0
1
Order By: Relevance
“…Therefore, the future recharge dynamics determined for the Annapolis Valley are assumed to be similar to those of the present study sites. Rivard et al (2014) found that all scenarios predict an annual recharge to the aquifer within the range of +14 to +45 % higher than at present by 2041-2071. They also predict, on a seasonal basis, that recharge will undergo (i) a marked decrease in summer (from 4 to 33 %) and (ii) a spectacular increase in winter (more than 200 %), due to an earlier melt period starting date.…”
Section: Recharge Evolutionmentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, the future recharge dynamics determined for the Annapolis Valley are assumed to be similar to those of the present study sites. Rivard et al (2014) found that all scenarios predict an annual recharge to the aquifer within the range of +14 to +45 % higher than at present by 2041-2071. They also predict, on a seasonal basis, that recharge will undergo (i) a marked decrease in summer (from 4 to 33 %) and (ii) a spectacular increase in winter (more than 200 %), due to an earlier melt period starting date.…”
Section: Recharge Evolutionmentioning
confidence: 99%
“…Over this period, recharge is adjusted to fit the calculated lake isotopic compositions to those measured. In the second step, the results of Rivard et al (2014) was chosen for the simulation of recharge scenarios, since this study focusses on the Annapolis Valley (Nova Scotia, Canada), not far from southern Quebec and with a similar latitude, geology, and climate. Therefore, the future recharge dynamics determined for the Annapolis Valley are assumed to be similar to those of the present study sites.…”
Section: Recharge Evolutionmentioning
confidence: 99%
See 3 more Smart Citations